2014
DOI: 10.1007/s12288-014-0379-z
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Spherocytosis: Evaluation of 68 Children

Abstract: To determine the clinical and hematologic features of 68 children with hereditary spherocytosis (HS). In this retrospective study, we analyzed recorded information of 68 HS patients diagnosed between March 1997 and March 2007, including clinical manifestations at admission, gender, median age at diagnosis, family history, hematologic and biochemical data, patient management, complications, median age of splenectomy, and median follow-up time. Sixty-eight patients with HS (36 male and female) were investigated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
(39 reference statements)
2
7
0
2
Order By: Relevance
“…We did not find any mutations in the EPB42 and SPTA1 genes, which were thought to be related to the sample size. Genetic studies on HS in Turkey are very limited, and there are only descriptive studies including clinical pathological phenotypes (22,23). To our knowledge, this is the first report to describe the mutational spectrum in Turkish children affected by HS.…”
Section: Discussionmentioning
confidence: 97%
“…We did not find any mutations in the EPB42 and SPTA1 genes, which were thought to be related to the sample size. Genetic studies on HS in Turkey are very limited, and there are only descriptive studies including clinical pathological phenotypes (22,23). To our knowledge, this is the first report to describe the mutational spectrum in Turkish children affected by HS.…”
Section: Discussionmentioning
confidence: 97%
“…Güngör et al10 recently evaluated 65 Turkish patients with HS and reported the median age of diagnosis at 48 months. Konca et al11 performed a study of 68 children with HS and found the age of diagnosis between 3 months and 18 years with a median of around 67 months.…”
Section: Discussionmentioning
confidence: 99%
“…In a few reports, recombinant erythropoietin (rEPO), or long-acting darbepoetin therapy has been used as an alternative or adjunct to transfusion [9]. Folic acid supplementation is recommended in treating HS [10,11] These children should be closely observed for hematologic decompensation during acute illnesses as some of them may experience hemolytic or aplastic crises. This outcome is particularly true after 6 months of age when maternally derived immunoglobulin G antibodies to microbes have waned.…”
Section: Hereditary Spherocytosis Diagnosis and Managementmentioning
confidence: 99%